Safety Exposure‐Response Analysis for Daclatasvir, Asunaprevir, and Beclabuvir Combinations in HCV‐Infected Subjects. (19th December 2018) - Osawa, Mayu; Ueno, Takayo; Shiozaki, Tomomi; Li, Hanbin; Garimella, Tushar
Abstract: The combination regimen of daclatasvir, asunaprevir, and beclabuvir has been developed for the treatment of hepatitis C virus infection. The objectives of this analysis were to characterize the relationship between the exposures of the daclatasvir, asunaprevir, and beclabuvir regimen and liver‐related laboratory elevations (Grade 3 or 4 alanine aminotransferase [ALT] and total bilirubin [Tbili]), and to evaluate the impact of selected covariates on the exposure‐response relationships. The exposure‐response analysis was performed with data from 1 phase 2 and 3 phase 3 studies in hepatitis C virus–infected subjects. The probability of liver‐related laboratory elevations were modeled using linear logistic regression. Selected covariates were tested using a forward‐addition and backward‐elimination approach. The final model for ALT elevation included Asian race, body weight in non‐Asian subjects, and asunaprevir exposure. The final model for Tbili elevation included Asian race, fibrosis score (F0‐F3 or F4) and asupanprevir exposure. Asian subjects had greater the Grade 3 or 4 ALT and Tbili elevation rates than non‐Asians. The Grade 3 or 4 ALT elevation rate increased with decreasing body weight in non‐Asian subjects. Subjects with F4 fibrosis score had a higher rate of Grade 3 or 4 Tbili elevation compared to subjects with F0 to F3 fibrosis score. Higher asunaprevir exposure was associated with increases in Grade 3 or 4 ALT and Tbili elevation rates; however, the impact on the ALT elevation was not clinically relevant and the effect on Tbili elevation was smaller than the other significant covariates.